The Status of Elderly People in Nepal - Aryal, Gokarna Raj (Patan Pragya, 2019)
Elderly citizens are the sources of knowledge, experiences and collections of different ideas in every society or nation. If we use their ability, long experiences and their conscience, our society or nation will be benefitted to reform national development and prosperity. Ageing population is a global phenomenon and the number is rapidly increasing in developing countries as compared to developed countries. The government of Nepal has declared that people with 60 years or more are elderly citizens. The growth rate of the elderly population is faster than that of the total population in Nepal. The observation shows that the proportion of elderly population is high in mountain and hilly regions as compared to Terai. However, it is noted that female elderly population is the highest among three ecological regions. The growing numbers of ageing population is a major concern in most of the developing countries like Nepal. The social, economic and demographic impacts of ageing population possess both opportunities and challenges to every society. In this situation, the Government of Nepal should attempt to enhance the self-reliance and provide social security of its elderly people to facilitate their continuous participation in society. The Government of Nepal has introduced the universal old aged allowances program since 1994/95 as a non-contributing social assistance to elderly citizens with 70 years or more. The starting allowances are nominal. At present context, it is not a sufficient amount for the elderly citizens but they have little support to health care, medicine, entertainment and desired foods and fruits. Likewise, the Government should establish old age homes, day care and ageing centers and parks for entertainment.